An Artificial Life - van Helmond, Wiet (Homœopathic Links, 2018)
A birds-eye perspective view on the health effects of artificial living as it is presently in many western countries and in this case specifically the Netherlands.
Keywords: Artificial life; Convalescence remedies; Reconnecting; Silica terra; Bacillus Gaertner Bach; Lycopodium clavatum; Okoubaka; Moonstone; Saccharum officinalis; Berlin wall